Upaya Menekan Risiko Hipertensi Melalui Konseling Pola Hidup Sehat di Desa Asrikaton Kabupaten Malang - Ahmad Taufiqurrohman Al Rosyid; Alifya Ines Berliana Apsari; Mochamad Lailul Fadlan; Ulil Fitriyah; Eny Yulianti (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2024)
Hypertension poses a significant health concern in various communities, including the rural setting of Asrikaton Village in Malang Regency. This research aims to evaluate and analyze efforts to mitigate the risk of hypertension through medical examinations and counseling on healthy lifestyle patterns in Asrikaton Village. The research methodology employs a mixed-method approach with both primary and secondary data collection. Medical examinations and family counseling take center stage, involving an educational approach to promote healthy lifestyles, stress management, and the cultivation of positive relationships within families. The research findings reveal a high incidence of hypertension, with 60% of the 60 participants affected, underscoring the urgency for serious attention. One approach to address this issue is through educational counseling on healthy lifestyles. The counseling aims to create healthy families by providing necessary information and support, particularly through the dissemination of knowledge and education on healthy lifestyles. This encompasses dietary habits, avoiding hypertension-triggering foods, incorporating regular physical activity into daily routines, and fostering a mindset that minimizes stress. By integrating both medical examinations and counseling on healthy lifestyles, it is anticipated that this program will foster a supportive environment, resulting in healthier families and enabling individuals with hypertension to lead normal and productive lives.